Accuracy and Reproducibility of the Peritoneal Cancer Index in Advanced Ovarian Cancer During Laparoscopy and Laparotomy. Issue 9 (1st November 2013) - Gouy, Sébastien; Belghiti, Jérémie; Uzan, Catherine; Canlorbe, Geoffroy; Gauthier, Tristan; Morice, Philippe
Abstract : Background: The aim of this prospective study was to evaluate the accuracy of the peritoneal cancer index (PCI) between laparoscopy and laparotomy and to evaluate the reproducibility of this index between 2 surgeons (junior vs senior) in advanced-stage ovarian cancer (ASOC). In ASOC, the quality of cytoreductive surgery, which is the main prognostic factor, is correlated with the extent of the disease and thus with the PCI. The reliability of this scoring index between different surgeons during laparoscopy and laparotomy has not been investigated in this disease. Methods: Between April 2010 and October 2011, for each of the 29 patients undergoing complete cytoreductive surgery, 1 senior surgeon and 1 junior surgeon quantified the PCI score at 3 time points on the same day: during laparoscopy and during laparotomy, at the beginning and at the end. A concordance analysis was conducted with Bland and Altman's method and estimated by intraclass correlation coefficients. Results: There was high concordance of the PCI score between the junior and senior surgeons during the laparoscopic and laparotomic procedures: the mean differences were not significantly different from 0 ( P < 0.05) and 95% limits of agreement were ±3.5 and ±3.0, respectively. Laparoscopy underestimated the PCI score by approximately 2 points compared to the beginning of the laparotomy: the mean biases were −2.0 (95% confidence interval, −2.8 to −1.2) for the senior surgeon and −2.2 (95% confidence interval, −3.1 to 1.3) for the junior surgeon. Conclusions: The PCI is reproducible and reliable for evaluating peritoneal spread in ASOC.